Development of a robust method for generating 7.0 T multichannel phase images of the brain with application to normal volunteers and patients with neurological diseases - Hammond, Kathryn E.; Lupo, Janine M.; Xu, Duan; Metcalf, Meredith; Kelley, Douglas A.C.; Pelletier, Daniel; Chang, Susan M.; Mukherjee, Pratik; Vigneron, Daniel B.; Nelson, Sarah J. (NeuroImage (Orlando, Fla.), 2008)
The increased susceptibility effects and high signal-to-noise ratio at 7.0 T enable imaging of the brain using the phase of the magnetic resonance signal. This study describes and evaluates a robust method for calculating phase images from gradient-recalled echo (GRE) scans. The GRE scans were acquired at 7.0 T using an eight-channel receive coil at spatial resolutions up to 0.195 × 0.260 × 2.00 mm. The entire 7.0 T protocol took less than 10 min. Data were acquired from forty-seven subjects including clinical patients with multiple sclerosis (MS) or brain tumors. The phase images were post-processed using a fully automated phase unwrapping algorithm that combined the data from the different channels. The technique was used to create the first phase images of MS patients at any field strength and the first phase images of brain tumor patients above 1.5 T. The clinical images showed novel contrast in MS plaques and depicted microhemorrhages and abnormal vasculature in brain tumors with unsurpassed resolution and contrast.